2021
DOI: 10.3897/pharmacia.68.e71460
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols content of selected medical plants and food supplements present at Bulgarian market

Abstract: Background: Medicinal plants are a rich source of antioxidant polyphenols and in particular flavonoids. Materials and methods: In the present study 5 Bulgarian medical plants and 5 food supplements, present at the Bulgarian market, are analyzed for their Total phenolic, Total flavonoids and selected individual flavonoids content. A HPLC method was developed and validated for simultaneous determination of (+)-catechin, (-)-epicatechin and rutin in plant and supplements, using PDA detection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The phenolic compounds were assessed by the HPLC method described by Filip et al [21]. Several studies have demonstrated that high-performance liquid chromatography (HPLC) is the most efficient technique for the qualitative and quantitative determination of polyphenolic compounds in plants, due to its high selectivity and precision [12,[22][23][24][25][26][27][28].…”
Section: Quantitative Analysis Of Phenolic Compounds In Elderflowersmentioning
confidence: 99%
“…The phenolic compounds were assessed by the HPLC method described by Filip et al [21]. Several studies have demonstrated that high-performance liquid chromatography (HPLC) is the most efficient technique for the qualitative and quantitative determination of polyphenolic compounds in plants, due to its high selectivity and precision [12,[22][23][24][25][26][27][28].…”
Section: Quantitative Analysis Of Phenolic Compounds In Elderflowersmentioning
confidence: 99%
“…All measurements in the present study were performed in triplicate and the methods were validated, according ISO 17025 requirements [24].…”
Section: Hplc Determination Of (+)-Catechin (-)-Epicatechin and Rutinmentioning
confidence: 99%
“…За определяне на общите феноли е използван реагент на Фолин-Чикалто, окисляващ фенолатите до син комплекс, който се определя спектрофотометрично при дължина на вълната λ=750 nm (8). Резултатите са изразени като галова киселина еквивалент (mg GAE/100 ml).…”
Section: определяне на общи фенолиunclassified